2007
DOI: 10.1653/0015-4040(2007)90[309:tbodfl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Diatraea Flavipennella (Lepidoptera: Crambidae) Reared Under Laboratory Conditions

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
(4 reference statements)
1
14
0
2
Order By: Relevance
“…Folegatti et al (1990), when evaluating the pathogenicity of M. anisopliae on A. flavipes adults, found that this fungus caused low mortality. Similar results were obtained by Hayashida et al (2012), who found low pathogenicity when testing higher concentrations of M. anisopliae on C. flavipes adults.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Folegatti et al (1990), when evaluating the pathogenicity of M. anisopliae on A. flavipes adults, found that this fungus caused low mortality. Similar results were obtained by Hayashida et al (2012), who found low pathogenicity when testing higher concentrations of M. anisopliae on C. flavipes adults.…”
Section: Resultssupporting
confidence: 87%
“…Pests are one of the main factors limiting sugarcane production. The species Diatraea flavipennella, known as the borer of yellow head, is considered an important pest causing injuries in sugarcane similar to those caused by Diatraea saccharalis (FREITAS et al, 2007). Its distribution, unlike D. saccharalis (which is widespread in Brazil), is restricted mainly to the northeastern states of the country (FREITAS et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Constitui um produto agrícola de grande utilização desde a produção do açúcar e álcool, até a alimentação animal. Um dos grandes impasses enfrentados por esta cultura, é a susceptibilidade durante todo o seu desenvolvimento ao ataque das brocas da cana-de-açúcar do gênero Diatraea que, normalmente, ocorre em menor incidência quando a cana é jovem, aumentando consideravelmente sua infestação com o desenvolvimento da planta (Gallo et al, 2002;Freitas et al, 2007).…”
Section: Introductionunclassified
“…Além disso, na região Nordeste, onde há predominância de D. flavipennella, estudos acerca do desempenho de T. galloi sobre essa espécie, e que os relacionem com sua espécie similar, D. saccharalis, são escassos (Freitas et al, 2007;Dinardo-Miranda et al, 2010). Uma das causas pelas quais estudos com D. flavipennella são reduzidos é a dificuldade de manutenção da criação em laboratório, uma vez que essa espécie apresenta um ciclo longo e desuniforme.…”
Section: Introductionunclassified